إستراتيجية التذكرية في تعلم اللغة العربية وتطبيقها - Muhammad Solihin (PROCEEDING AL GHAZALI International Conference, 2024)
In achieving the highest educational in Arabic language needs an appropriate strategy. In this study the writer explains how to apply the memory strategy in teaching and learning Arabic. In this paper, the writer uses memory strategies as a basic foundation in compling effective material. Many students in institutes and schools are not able to know the meanings of the Arabic word and vocabulary because they are not using the memory strategy. Therefore, in overcoming this problem, students need a memory strategy in learning Arabic in order to focus on the thinking process to strengthen memory through the repetition process so that they get good and maximum results. Oxford said that the second language teaching strategy is a set of steps and procedures that students take in learning a language.